Investigation of the graphitization process of ion-beam irradiated diamond using ellipsometry, Raman spectroscopy and electrical transport measurements. (September 2017) - Lühmann, T.; Wunderlich, R.; Schmidt-Grund, R.; Barzola-Quiquia, J.; Esquinazi, P.; Grundmann, M.; Meijer, J.
Abstract: Amorphous thin films were produced embedded in a diamond matrix by high energy He + -ion irradiation. The films were subsequently annealed at different temperatures up to graphitization and characterized by spectroscopic ellipsometry, Raman spectroscopy and electrical transport measurements. Changes of the optical constants depending on the annealing temperature were observed and using the optical effective-medium-approximation-model (EMA), assuming stochastic packing of hard spheres and a grain size estimate from the Raman results, an average distance between the spheres of about 6 Å was found. This distance can be correlated with the localization length parameter of the variable range hopping transport mechanism obtained from resistance measurements. Graphical abstract: